Strategic collaboration between AUSC-FISU Oceania to strengthen the development of university sports in Malaysia - Mohd Aznorizamin, Ismail (UMPSA, 2023)
GENEVA, 18 November 2023 - The strategic collaboration between the ASEAN University Sports Council (AUSC) and FISU Oceania is set to strengthen the development of university sports in Malaysia.